2007
DOI: 10.1021/jo062320s
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular PIFA-Mediated Alkyne Amidation and Carboxylation Reaction

Abstract: The hypervalent iodine reagent PIFA promotes the intramolecular electrophilic cyclization of easily accessible alkynylamides and alkynyl carboxylic acids, leading to the formation of pyrrolidinone and lactone skeletons, respectively, in a very efficient way. A synthetic study and a mechanistic proposal for these transformations are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…The reaction mixture was acidified to pH 2 using 2M aqueous HCl and extracted with Ethyl-4-pentynoate was prepared following reported procedures. 39 …”
Section: Synthesis Of 22-dimethylpent-4-ynoic Acid (3)mentioning
confidence: 99%
“…The reaction mixture was acidified to pH 2 using 2M aqueous HCl and extracted with Ethyl-4-pentynoate was prepared following reported procedures. 39 …”
Section: Synthesis Of 22-dimethylpent-4-ynoic Acid (3)mentioning
confidence: 99%
“…To determine the effect of the electronic state of the ester of the outcome of the reaction, we also investigated several non-and monosubstituted benzoyl groups. The results of these reactions revealed that the use of an aromatic ring bearing an electronwithdrawing group gave a better yield than an aromatic ring bearing an electron-donating group or no substituent at all ( Table 2, entries [15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Based on the importance of α-acyloxyketones to chemistry, the development of a concise synthetic method for the preparation of α-acyloxyketone derivatives is important. Although a wide variety of synthetic methods have been investigated to date, 12,13) reports pertaining to the direct synthesis of α-acyloxyketone III by the oxidation of alkyne I are rare, most likely because of the difficulties associated with suppressing the over-oxidation of the product and controlling the regioselectivity of the reaction [14][15][16] (Chart 1). To allow for the direct synthesis of α-acyloxyketone III from alkyne I, several researchers directed their attention towards the transition metal-catalyzed migration of propargylic esters [17][18][19][20] to affect a facile oxidative transformation.…”
mentioning
confidence: 99%
“…6,7 Therefore, directed toward the development of the metal-free cycloisomerization/functionalization sequence of N-propargyl amides, we have focused on the activation mechanism by PIFA and the reductive elimination of iodobenzene (Scheme 2). 4 Thus, the similar properties of λ 3 -iodane to metal catalyst would be expected to lead to the metal-free formation of oxazoles concomitant with the introduction of oxygen functional groups.…”
Section: Synthesis Of Oxazoles By Cycloisomerization/oxy-functionalizmentioning
confidence: 99%
“…In addition to the abovementioned reactions, Tellitu and Domínguez's group have reported that phenyliodine(III) bis(trifluoroacetate) (PIFA) directly promote the oxidative cyclization of 4-alkynylcarboxamides (Scheme 2). 4 In this procedure, PIFA works not only as a donor of oxygen function group but also as an activator for the triple bond (R' = alkyl). However, the similar approach to the aromatic heterocycles by λ 3 -iodanes had not been reported, although oxidative cycloisomerization of enynols by 2-Iodoxybenzoic Acid (IBX) had been known as the facile synthesis of 2-acylfurans.…”
Section: Introductionmentioning
confidence: 99%